A Case Study of Near‐Earth Magnetotail Conditions at Substorm and Pseudosubstorm Onsets. Issue 13 (12th July 2018) - Miyashita, Y.; Angelopoulos, V.; Fukui, K.; Machida, S.
Abstract: While a substorm involves auroral poleward expansion after initial brightening, a pseudosubstorm (pseudobreakup) subsides without progressing to poleward expansion. To understand what makes this difference, we studied near‐Earth magnetotail conditions at a pseudosubstorm onset and the subsequent substorm onset, using multipoint Time History of Events and Macroscale Interactions during Substorms spacecraft data. In the present event, near‐Earth magnetic reconnection possibly occurred before initial brightening for both pseudosubstorm and substorm. In the near‐Earth magnetotail at X ∼− 10  R E, the ion β, ion pressure, and ion and total (ion plus magnetic) pressure gradient projection along two closely located spacecraft were smaller and magnetic field lines were less stretched around the pseudosubstorm initial brightening than around the substorm initial brightening. Dipolarization did not occur for the pseudosubstorm, whereas it began just before poleward expansion for the substorm. These observations suggest that conditions of the near‐Earth magnetotail possibly affect whether the initial action develops into a full‐fledged substorm. Plain Language Summary: A pseudosubstorm, also called pseudobreakup, is an auroral phenomenon very similar to a substorm but essentially differs in absence of active auroral expansion. In this paper, we studied conditions of the magnetotail at the beginning of these auroral phenomena on the basis of spacecraft observations. This comparison is expected to give us some clues to understanding of substorm triggering and development mechanisms. We found that plasma and magnetic field conditions in the magnetotail differed between the two auroral phenomena. This finding implies that magnetotail conditions possibly affect auroral development. Key Points: We compared near‐Earth magnetotail conditions at a pseudosubstorm onset and the subsequent substorm onset The pressure gradient and ion beta in the near‐Earth magnetotail were smaller for the pseudosubstorm than for the substorm We suggest that near‐Earth magnetotail conditions possibly affect whether the initial action develops into a full‐fledged substorm